2012
DOI: 10.1590/s0001-37652012005000045
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine cells and nerve ganglia of the small intestine of the Opossum Didelphis aurita Wied-Neuwied, 1826 (Mammalia: Didelphidae)

Abstract: The nervous and endocrine systems jointly control intestinal movements, secretions of their glands and also participate of the processes of nutrient digestion and absorption. Therefore, the central objective of this study was to verify the existence of a possible relationship between the number of nervous cells and ganglia of the submucosal and myenteric plexuses and the number of endocrine cells in the small intestine of adult D. aurita. The utilized staining techniques were Grimelius, modified Masson-Fontana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…These data indicate that the administration of probiotics during the initial phases of the digestive system development seems to be important to drive the correct functionality of intestine, as also observed by other authors (Preidis et al 2012). The study on how the nervous and endocrine systems interact with the small intestine by controlling its functions was addressed by Freitas-Ribeiro et al (2012) using Didelphis aurita as a model for enteroendocrine cells. The authors demonstrated that the distribution of endocrine and nerve ganglia in the small intestine followed the same morphology encountered in other eutherian mammals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicate that the administration of probiotics during the initial phases of the digestive system development seems to be important to drive the correct functionality of intestine, as also observed by other authors (Preidis et al 2012). The study on how the nervous and endocrine systems interact with the small intestine by controlling its functions was addressed by Freitas-Ribeiro et al (2012) using Didelphis aurita as a model for enteroendocrine cells. The authors demonstrated that the distribution of endocrine and nerve ganglia in the small intestine followed the same morphology encountered in other eutherian mammals.…”
mentioning
confidence: 99%
“…The study on how the nervous and endocrine systems interact with the small intestine by controlling its functions was addressed by Freitas-Ribeiro et al (2012) using Didelphis aurita as a model for enteroendocrine cells. The authors demonstrated that the distribution of endocrine and nerve ganglia in the small intestine followed the same morphology encountered in other eutherian mammals.…”
mentioning
confidence: 99%